The ecological role of elephants in Africa - David Western (Pachyderm)
Addresses the problems associateed with ecological arguments for conserving species, and notes these arise because the ecological role of a species is rarely obvious to non-ecologists, and that it is difficult to show the consequences of losing a species until after it is gone. A number of examples of the keystone role of elephants in African ecosystems are cited. The Amboseli example in Kenya illustrates what happens to biological diversity when through time in relationship to a widely varying population of elephants. Various ecological roles of elephants such as agents of seed dispersal, creators of openings or gaps in forest areas are discuss.